Educación financiera y nivel de endeudamiento en los comerciantes del mercado del Campo Ferial de Contamana 2025 - Vela Flores, Arthur Christian (2025)
The study aimed to determine the relationship between financial literacy and debt levels among merchants at the Contamana 2025 Fairgrounds market. A basic, descriptive methodology and non-experimental design were used. The sample consisted of 70 merchants. The findings revealed that the merchants' financial literacy level was average (26%), mainly because they only occasionally reviewed and adjusted their personal budget to understand how and where they spent their money. Furthermore, they almost always carefully monitored the inflows and outflows of money in both their businesses and their personal lives, and made decisions to avoid spending more than they earned. Similarly, their debt level was determined to be average (27%), because they occasionally made their bank payments according to schedule and, in some cases, held loans from two or more financial institutions. In conclusion, the correlation test showed a coefficient of 0.847, demonstrating a very strong positive correlation between financial literacy and debt levels, with statistical significance at the 0.01 level.